Suicide ideation in multiple sclerosis Egyptian patients: neurologic and psychiatric correlates - Nesma A. M. Ghonimi; Rania H. Elbaz; Mohammed E. Mahdy; Shaimaa A. Elaidy (Middle East Current Psychiatry)
Abstract Introduction Depression frequently occurs in multiple sclerosis (MS) patients and is encountered to be the major contributing factor for suicidal ideation (SI); however, limited reports are available about this issue. Our study’s aim was to investigate depression, suicidal ideation, and their risk factors in Egyptian MS patients. Methods One hundred forty-nine patients with MS were evaluated by Beck Scale for Suicide Ideation (BSI), Beck Depression Inventory (BDI), and the Expanded Disability Status Scale (EDSS). Results Our findings show that 64.4% of studied MS patients had low suicide risk while 35.6% showed high suicide risk. Suicidal ideation was associated with being unmarried, unemployed, progressive disease, longer duration of illness, depression, and higher physical disability. In binary logistic regression, only severity of depression and degree of disability were independently associated with suicidal ideation (P < 0.001). Conclusions Our results suggest that depression has a major weight on the risk of suicide in MS patients and throw light on the importance of regular screening and early appropriate treatment for such comorbidity to avoid its negative outcomes.